FAKTOR-FAKTOR YANG MEMENGARUHI KINERJA USAHA WANITA WIRAUSAHA PADA INDUSTRI MAKANAN RINGAN DI PROVINSI SUMATERA BARAT - Amri Syahardi; Lukman Mohammad Baga; Ratna Winandi (Forum Agribisnis, 2017)
Women entrepreneurs as the family support unit that plays a role in increasing the family income, has a performance which is still low compared to male entrepreneurs. The purpose of this study was to analyze (1) the profile of women entrepreneurs and snack food industry; (2) the influence of personal characteristics, internal and external business environment, as well as entrepreneurial behavior to business performance of women entrepreneurs. This study used survey method that conducted  in Limapuluh Kota Regency and Payakumbuh City. Structural Equation Modeling (SEM) was used for descriptive and quantitative analysis. The respondents used were 105 women entrepreneurs. The results showed that: (1) women entrepreneurs engaged in the snack food industry in West Sumatera in general are in the productive age above 40 years, the business managed by women entrepreneurs in general is still relatively small business with income average of Rp1.687.000 per week; (2) the personal characteristics, internal environment of business, external environment of business, and the entrepreneurial behaviour has positive and significant influence to business performance. The most dominant personal characteristics which influence the business performance were education and family background, the most dominant  internal environment which influence business performance was financial aspect, the most dominant external environment which influence business performance was marketing and the most dominant entrepreneurial behavior influences the business performance was innovation. Women entrepreneurs were encouraged to improve human resources and risk taking by borrowing capital to develop the business.